A Comparison of Surgical Treatments for Superior Semicircular Canal Dehiscence: A Systematic Review. Issue 1 (January 2017) - Ziylan, Fuat; Kinaci, Ahmet; Beynon, Andy J.; Kunst, Henricus P. M.
Abstract : Objective: We investigate the postoperative subjective and objective outcomes of different surgical treatments for superior semicircular canal dehiscence (SSCD): vestibular signs, auditory signs, vestibular evoked myogenic potential test, pure tone audiogram, speech audiogram, or video-nystagmography. Data Sources: An electronic search performed in the PubMed, Cochrane Library, and EMBASE databases on 15th of September 2015. A systematic search was conducted. Articles were included if written in English, Dutch, German, or French language. Study Selection: Original studies reporting on the pre and postoperative subjective and/or objective outcomes of surgical treatments for superior semicircular canal dehiscence were included. Data Extraction: The methodological quality of the studies was independently assessed by two reviewers using a constructed critical appraisal, to assess the directness of evidence and the risk of bias. The results of the pre and postoperative subjective and/or objective outcomes were extracted. Data Synthesis: Comparative study was conducted. Conclusion: Surgical treatment for SSCD is particularly effective for vestibular symptoms and there is no evidence for improvement of hearing loss after surgical treatment. Since plugging using transmastoid approach had a lower complication rate, lower revision rate, and a shorter hospital stay, this treatment is recommended in high disabled SSCD patients. Abstract : Supplemental Digital Content is available in the text